The Metamorphosis of Low German – Between Decline and Persistence - Iliescu, Maria-Sânziana (Universitatea Transilvania Brasov, 2025)
The decline of Hanseatic power led to a decrease in the importance of Low German as a language of trade and culture within the Hanseatic region. Today, however, the targeted variety is primarily encountered as a spoken regional language, which is attributed an important artistic dimension thanks to Low German theater, as well as a component of the contemporary supraregional standard language. Moreover, Low German has been recognized as an intangible UNESCO World Cultural Heritage. It becomes evident that the subject of this study is shaped by the complex interplay between archaisation and revitalization. The focus of the present investigation lies in identifying the reasons that have accelerated and facilitated lexical loss. Its multifaceted nature is examined from an interdisciplinary perspective, so that both sociolinguistic factors and cognitive and language-internal mechanisms can be considered as causes for the decline of certain linguistic phenomena. In addition, the influence of Low German will be demonstrated using a contemporary corpus.
Keywords: Lexical Decline; Low German; Middle Low German; Hanseatic Region; Plattdeutsch